La forma del sociale: Kelsen, Freud e Thomas a confronto - Chiaramonte, Xenia (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
How does the social take shape? Beginning with a joint reading of Kelsen’s and Freud’s thought, and in particular, from Der Begriff des Staates und die Sozialpsychologie. Mit besonderer Berücksichtigung von Freuds Theorie der Masse (1922) and Massenpsychologie und Ich- Analyse (1921) respectively, the question will be answered through the research and “method” of Yan Thomas. The comparison between the three authors allows us to illuminate the libidinal form of society as well as the legal form, both as attempts to respond to the still too naturalistic concept of the social bond. Here the concept of coercion (Zwang) plays a decisive role, particularly for Kelsen and Freud who propose a social model that has the features of the penal. By conflating the concept of coercion with a “civil” genealogy, however, Thomas can open up a new glimpse into the form of the social.